2015
DOI: 10.1002/pits.21822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teacher-Student Relationships on Peer Harassment: A Multilevel Study

Abstract: Peer harassment is a major social problem affecting children and adolescents internationally. Much research has focused on student-to-student harassment from either an individual or a multilevel perspective. There is a paucity of multilevel research on students' relationships with the classroom teacher. The purpose of this study was to use a socioecological perspective to examine the relationships between individual student-level characteristics, problematic teacher-student relationships, and student-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 52 publications
4
29
0
10
Order By: Relevance
“…As a first step toward addressing this aim, we were interested in assessing whether teacher-student relationships were associated with PV and psychosocial distress. Consistent with established findings, we hypothesized that teacherstudent relationships would be negatively related to PV (e.g., Elledge et al, 2016;Lucas-Molina et al, 2015;Mann et al, 2015). Similarly, and consistent with a social support theoretical framework and literature indicating that teacherstudent relationships can protect against adversity more generally (e.g., Baker et al, 2008;Opdenakker, Mualana, & den Brok, 2012), we also hypothesized that teacher-student relationships would be negatively related to psychosocial distress.…”
Section: The Current Studysupporting
confidence: 74%
See 1 more Smart Citation
“…As a first step toward addressing this aim, we were interested in assessing whether teacher-student relationships were associated with PV and psychosocial distress. Consistent with established findings, we hypothesized that teacherstudent relationships would be negatively related to PV (e.g., Elledge et al, 2016;Lucas-Molina et al, 2015;Mann et al, 2015). Similarly, and consistent with a social support theoretical framework and literature indicating that teacherstudent relationships can protect against adversity more generally (e.g., Baker et al, 2008;Opdenakker, Mualana, & den Brok, 2012), we also hypothesized that teacher-student relationships would be negatively related to psychosocial distress.…”
Section: The Current Studysupporting
confidence: 74%
“…In another recent cross‐sectional study that was conducted with a large sample of students in Spain ( N = 1,864; ages 8–12 years), Lucas‐Molina, Williamson, Pulido, and Pérez‐Albéniz () found that teacher support was associated with reductions in student‐reported PV. Additionally, hostile teacher–student relationships were found to be associated with higher levels of PV at school.…”
Section: Teacher–student Relationshipsmentioning
confidence: 99%
“…Moreover, teacher‐student relationships have been shown to affect student behavior during childhood and adolescence on several outcomes. For instance, children who perceive their teachers as supportive report less victimization (i.e., harassment) by peers and those who have problematic relationships with their teachers report experiencing greater victimization (Lucas‐Molina, Williamson, Pulido, & Pérez‐Albéniz, ). Furthermore, adolescents who perceive social support from their teachers experience greater life satisfaction and less psychopathology in the form of externalizing behaviors (Stewart & Suldo, ).…”
mentioning
confidence: 99%
“…Vzdolžna raziskava viktimizacije (Troop-Gordon in Kopp, 2011) je pokazala, da pozitivni odnosi med učenci in učitelji ne varujejo učencev pred pojavom viktimizacije. Hkrati raziskovalni izsledki kažejo na pomembno vlogo negativnih odnosov med učenci in učitelji, ki so povezani z višjo stopnjo medvrstniške viktimizacije v šolskem okolju (Lucas-Molina, Williamson, Pulido in Perez-Albeniz, 2015). Če učenci poročajo o slabšem odnosu z učitelji, to vpliva na to, da so bolj ranljivi za doživljanje psihičnega distresa ob doživljanju viktimizacije (Sulkowski in Simmons, 2017).…”
Section: Dejavniki Na Ravni Odnosov Z Učiteljiunclassified
“…Pozitivni odnosi z učitelji so lahko pozitiven napovednik viktimizacije v primeru, ko drugi učenci te odnose označujejo negativno, kar lahko spodbudi zbadanje učencev, ki se z učitelji dobro razumejo. Negativni odnosi z učitelji so se pokazali kot izjemno pomemben napovednik viktimizacije, in sicer slabši, kot so zaznani odnosi z učitelji, višja je poročana stopnja viktimizacije, kar je skladno z rezultati predhodnih raziskav, kjer je bilo prav tako ugotovljeno, da negativni odnosi z učitelji kažejo na večjo verjetnost, da so učenci deležni nasilja (Lucas-Molina et al, 2015;Marengo et al, 2018). Pri raziskovanju viktimizacije in odnosov z učitelji je bilo prav tako predpostavljeno, da za preprečevanje doživljanja nasilja pri učencih ni nujno, da imajo pozitivne odnose z učitelji, ampak je dovolj to, da so odnosi med njimi ustrezni in da jih učenci ne označujejo kot negativne (Sulkowski in Simmons, 2017), kar učiteljem omogoča, da vplivajo na razredno klimo, se učinkovito odzivajo na težave in pomagajo učencem, da se počutijo varne in sprejete, kar lahko pomaga pri zmanjševanju doživljanja nasilja med učenci (Jennings in Greenberg, 2009).…”
Section: Razpravaunclassified